PENGEMBANGAN LKPD IPA INTERAKTIF BERBASIS MODEL FERA DALAM PEMBELAJARAN SUHU, KALOR, DAN PEMUAIAN - Gusti Ngurah Andika Prayoga; Ni Made Pujani; Nia Erlina (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
The Independent Curriculum demands mastery of Science Process Skills, but the reality of classroom learning is still dominated by conventional methods due to time constraints and the lack of physical laboratory facilities in schools. The focus of this research is the high level of misconceptions among seventh-grade students regarding the abstract nature of temperature, heat, and expansion, necessitating media that can facilitate the needs of kinesthetic learning styles. This research aims to develop an Interactive Science Student Worksheet (LKPD) based on the FERA (Focus, Explore, Reflect, Apply) inquiry model in a hybrid format. The important stages of the research apply the Research and Development method through the ADDIE framework, which is limited to the analysis, design, and product development phases. Data were analyzed quantitatively using the Gregory Validity Coefficient formula and the calculation of the average score of the instrument. The research findings show that content validity achieved an absolute score of 1.00 from experts, meaning it is very feasible to use theoretically. Furthermore, a practicality test involving teachers and students obtained an average score of 4.80, with a predicate of very practical. The use of PhET virtual laboratory simulation technology in student worksheets (LKPD) has proven effective in reducing preparation time and significantly increasing student learning independence. The main conclusion confirms that this interactive LKPD based on the FERA model is highly adaptive and effective in correcting misconceptions and training students' scientific reasoning in a sustainable, systematic, and independent manner.